Sugarcane Ratooning Ability: Research Status, Shortcomings, and Prospects - Fu Xu; Zhoutao Wang; Guilong Lu; Rensen Zeng; Youxiong Que (Biology, 2021)
Sugarcane is an important sugar crop and it can be subjected to ratooning for several years. The advantages of ratooning include quality improvement, efficiency enhancement, and reduced costs and energy use. The genotype, environment, cultivation management, and harvesting technology affect the productivity and longevity of ratoon cane, with the genetic basis being the most critical factor. However, the majority of research has been focused on only limited genotypes, and a few studies have evaluated up to 100 sugarcane germplasm resources. They mainly focus on the comparison among different genotypes or among plant cane, different selection strategies for the first and second ratoon crops, together with screening indicators for the selection of stronger ratooning ability. In this paper, previous studies are reviewed in order to analyze the importance of sugarcane ratooning, the indicative traits used to evaluate ratooning ability, the major factors influencing the productivity and longevity of ratooning, the genetic basis of variation in ratooning ability, and the underlying mechanisms. Furthermore, the shortcomings of the existing research on sugarcane ratooning are highlighted. We then discuss the focus of future ratoon sugarcane research and the technical methods that will shorten the selection cycle and increase the genetic gain of ratooning ability, particularly the development of linked markers. This review is expected to provide a reference for understanding the mechanisms underlying the formation of ratooning ability and for breeding sugarcane varieties with a strong ratooning ability.